Electric transport through c-nanotubes and grapheme nanoribbons double quantum dots coupled by a superconductor (2014)
Abstract. Graphene has become a promising material for technological applications and research in fundamental physics due to its rich physical properties. A detailed study of its hexagonal crystalline structure has been performed and has revealed its unusual electronic properties of great interest in nanotechnology and quantum electronics[1, 2, 3]. Charge carriers exitations with energies near the Fermi can be approximated by an effective Weyl-Dirac Hamiltonian thus implying relativistic behavior. As a consequence, chiral or Klein tunneling is present in transport in which electrons can tunnel a barrier with unit probability. We will review the physical properties of bulk graphene, but we will concentrate in graphene nanoribbons and carbon nanotubes in zigzag configuration and their electronic properties[4]. While ideal nanoribbons are always metallic, a band gap arises as a consequence of the curvature in nanotubes due to overlap of perpendicular orbitals and spin-orbit coupling, thus manifesting semi-metallic and semiconducting regimes according to geometry parameters[5]. These curvature effects raise valley and spin degeneracies present in graphene therefore becoming a more suitable material for quantum control applications. In nanotubes, periodicity along circumferential direction implies quantization of transverse momentum and thus to 0-dimensional energy channels available for transport. Chiral tunneling reduces electronic confinement in metallic materials, but as the energy gap increases, separated regions of the same material can be decoupled by means of a electrostatic barrier, such as a series double quantum dot. In practice, transport through single-channel carbon nanotubes double quantum dos coupled in series and tunable in-situ has been measured and has revealed the processes involved in normal- to super-current conversion. Nonlocal components of transport, i.e., Andreev processes at separated regions, evidence the possibility of producing entangled electronic states in a 2-level molecular system (qubit), fundamental for quantum computation[6]. A minimal model of transport thorugh this device has shown that there under certain physical configurations the system can reach a splitting efficiency of about unity[7].